2021
DOI: 10.1021/acsapm.1c01519
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Model for Composite Stereolithography to Enable Resin–Filler Selection and Cure Depth Control

Abstract: Fillers are used to modify the properties of the photoresins used in stereolithography (SLA). The resulting composite formulations tend to have a decreasing cure depth for increasing particle loadings due to light scattering. However, some composites, such as those loaded with silica or polymethyl methacrylate particles, show the opposite effect: the cure depth increases with the particle loading. To unify these seemingly contradictory observations, we propose a modified Lambert–Beer equation. Depending on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…Apart from their advantages with respect to their CTE and Young's modulus values, the combination of silica and an Esun resin has another benefit compared to other filler/resin formulations. As SLA is a light-based technique, strong light scattering by the ceramic filler should be avoided by selecting refractive index-matching materials [56]. For this reason, a formulation of silica with Esun resin is better suited than alumina-Esun resin, silica-Formlabs resin, or alumina-Formlabs resin formulations [56].…”
Section: Materials Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from their advantages with respect to their CTE and Young's modulus values, the combination of silica and an Esun resin has another benefit compared to other filler/resin formulations. As SLA is a light-based technique, strong light scattering by the ceramic filler should be avoided by selecting refractive index-matching materials [56]. For this reason, a formulation of silica with Esun resin is better suited than alumina-Esun resin, silica-Formlabs resin, or alumina-Formlabs resin formulations [56].…”
Section: Materials Selectionmentioning
confidence: 99%
“…As SLA is a light-based technique, strong light scattering by the ceramic filler should be avoided by selecting refractive index-matching materials [56]. For this reason, a formulation of silica with Esun resin is better suited than alumina-Esun resin, silica-Formlabs resin, or alumina-Formlabs resin formulations [56]. The silica powder (SS1402, Industrial Powder, USA) has a density of ~2.2 g/cm 3 and a size of 2 µm (d 50 ); its shape and particle size distribution (PSD) can be found in Figs.…”
Section: Materials Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, composite fillers often absorb, refract, or scatter incident light, leading to the increase in the lightattenuation gradient. 17,18 Such extinction behaviors, especially in the case of a high filler content, intensively weaken the light penetration through the entire polymerizable medium and inhibits photopolymerization; these eventually lead to the deterioration of material performances, and therefore photopolymerization of highly filled systems remains a profound challenge. 19 In parallel, numerous studies have reported a growing interest in composites photopolymerization with a high filler content, including fabrication of high-performance or functional materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Photopolymers integrated with rich functional fillers may render fresh performance to the polymers, spanning from high mechanical properties and dielectric properties, refractive index, and electrical conductivity as well as multiple stimuli responsiveness. The functionalities of photopolymers are significantly improved with the increase of filler content. However, composite fillers often absorb, refract, or scatter incident light, leading to the increase in the light-attenuation gradient. , Such extinction behaviors, especially in the case of a high filler content, intensively weaken the light penetration through the entire polymerizable medium and inhibits photopolymerization; these eventually lead to the deterioration of material performances, and therefore photopolymerization of highly filled systems remains a profound challenge . In parallel, numerous studies have reported a growing interest in composites photopolymerization with a high filler content, including fabrication of high-performance or functional materials. , …”
Section: Introductionmentioning
confidence: 99%